The pancreatic cancer-initiating cell marker CD44v6 affects transcription, translation, and signaling: consequences for exosome composition and delivery - Sun, Hanxue; Rana, Sanyukta; Wang, Zhe; Zhao, Kun; Schnölzer, Martina; Provaznik, Jan; Hackert, Thilo; Lv, Qingjie; Zöller, Margot (Journal of oncology, 2019)
Pancreatic cancer-initiating cells (PaCIC) express CD44v6 and Tspan8. A knockdown (kd) of these markers hinders the metastatic capacity, which can be rescued, if the cells are exposed to CIC-exosomes (TEX). Additional evidence that CD44v6 regulates Tspan8 expression prompted us to explore the impact of these PaCIC markers on nonmetastatic PaCa and PaCIC-TEX. We performed proteome, miRNA, and mRNA deep sequencing analyses on wild-type, CD44v6kd, and Tspan8kd human PaCIC and TEX. Database comparative analyses were controlled by qRT-PCR, Western blot, flow cytometry, and confocal microscopy. Transcriptome analysis of CD44 versus CD44v6 coimmunoprecipitating proteins in cells and TEX revealed that Tspan8, several signal-transducing molecules including RTK, EMT-related transcription factors, and proteins engaged in mRNA processing selectively associate with CD44v6 and that the membrane-attached CD44 intracytoplasmic tail supports Tspan8 and NOTCH transcription. Deep sequencing uncovered a CD44v6 contribution to miRNA processing. Due to the association of CD44v6 with Tspan8 in internalization prone tetraspanin-enriched membrane domains (TEM) and the engagement of Tspan8 in exosome biogenesis, most CD44v6-dependent changes were transferred into TEX such that the input of CD44v6 to TEX activities becomes largely waved in both a CD44v6kd and a Tspan8kd. Few differences between CD44v6kd- and Tspan8kd-TEX rely on CD44v6 being also recovered in non-TEM derived TEX, highlighting distinct TEX delivery from individual cells that jointly account for TEX-promoted target modulation. This leads us to propose a model in which CD44v6 strongly supports tumor progression by cooperating with signaling molecules, altering transcription of key molecules, and through its association with the mRNA processing machinery. The association of CD44v6 with Tspan8, which plays a crucial role in vesicle biogenesis, promotes metastases by transferring CD44v6 activities into TEM and TEM-independently derived TEX. Further investigations of the lead position of CD44v6 in shifting metastasis-promoting activities into CIC-TEX may offer a means of targeting TEX-CD44v6 in therapeutic applications.
Gesehen am 28.01.2022